Mild matters: trial learnings and importance of community engagement in research for early identified bilateral mild hearing loss - Sung, Valerie; Ching, Teresa Y. C.; Smith, Libby; Marnane, Vivienne; Saetre-Turner, Michelle; King, Alison; Beswick, Rachael; Iseli, Claire E.; Carew, Peter (Frontiers in Pediatrics, 2023)
Early identification of mild hearing loss has resulted in early hearing amplification without adequate evidence of effectiveness. This paper describes learnings from a pilot trial, combined with a qualitative study, to highlight the importance of community engagement in designing research studies to determine whether early amplification benefits young children with bilateral mild hearing loss. PART 1 of the study is a proof-of-concept non-blinded multi-centre randomised controlled trial (RCT) of hearing device fitting versus no fitting aimed to gather preliminary data and determine its acceptability/feasibility in children <2 years old with bilateral mild hearing loss. Of 40 potentially eligible families, nine (23%) declined, three were uncontactable (7%), 26 (65%) ineligible: of these, nine (35%) did not meet hearing threshold inclusion criteria, 11 (42%) were already fitted or had made decisions on fitting hearing device, two (7%) had conductive loss and four (16%) were ineligible for other reasons. Two of 11 (18%) eligible families were randomised. With the limited sample size, outcome measures were not compared between groups. Both participants completed the trial, reported the RCT to be acceptable, and neither changed group post-enrolment. PART 2 is a qualitative study to understand the barriers/enablers to RCT participation. Whilst recruitment uptake could potentially be increased by altering the eligibility criteria, better communication with and reimbursement of clinicians as recruiters, and improving awareness of the study amongst external stakeholders, the RCT methodology does not conform to family-centred practice, and potentially raises ethical concerns regarding potential adverse consequences of not offering early amplification. Parental perception of losing control over choice of management due to randomisation is not an easily modifiable factor. Alternative methodological approaches without randomisation are required to determine whether hearing amplification benefits infants with mild hearing loss.